Mechanism and application of fermentation to remove beany flavor from plant-based meat analogs: A mini review - Tao, Anqi; Zhang, Hongyu; Duan, Junnan; Xiao, Ying; Liu, Yao; Li, Jianwei; Huang, Jieyu; Zhong, Tian; Yu, Xi (Frontiers in Microbiology, 2022)
Over the past few decades, there has been a noticeable surge in the market of plant-based meat analogues (PBMA). Such popularity stems from their environmentally friendly production procedures as well as their positive health effects. In order to meet the market demand, it is necessary to look for plant protein processing techniques that can help them match the quality of conventional meat protein from the aspects of sensory, quality and functionality. Bean proteins are ideal options for PBMA with their easy accessibility, high nutrient-density and reasonable price. However, the high polyunsaturated lipids content of beans inevitably leads to the unpleasant beany flavor of soy protein products, which severely affects the promotion of soy protein-based PBMA. In order to solve this issue, various methods including bleaching, enzyme and fermentation etc. are developed. Among these, fermentation is widely investigated due to its high efficiency, less harm to the protein matrix, targeted performance and low budget. In addition, proper utilization of microbiome during the fermentation process not only reduces the unpleasant beany flavors, but also enhances the aroma profile of the final product. In this review, we provide a thorough and succinct overview of the mechanism underlying the formation and elimination of beany flavor with associated fermentation process. The pros and cons of typical fermentation technologies for removing beany flavors are discussed in alongside with their application scenarios. Additionally, the variations among different methods are compared in terms of the strains, fermentation condition, target functionality, matrix for application, sensory perception etc.